Electronically tunable resistorless memtranstor emulator using CCCCTA and its application to secure image encryption - Sagbas, Mehmet; Minaei, Shahram; Cayir, Muzaffer; Ayten, Umut Engin (ELSEVIER, 2026)
In this work, a novel resistorless, electronically tunable memtranstor (MT) emulator is presented. The design employs Current Controlled Current Conveyor Transconductance Amplifiers (CCCCTAs) and an analog multiplier as active components, together with grounded capacitors as the passive elements. In the proposed configuration, the relationship between charge and flux is electronically controlled via the transconductance (gm) and parasitic resistance (Rx) parameters of the CCCCTAs through their bias currents. The memtranstor emulator is designed in a grounded topology, offering advantages in integration and stability. Using TSMC 0.18 mu m CMOS technology parameters, comprehensive PSpice simulations were conducted to evaluate the performance of the suggested circuit. The dynamic behavior of the emulator was investigated under varying frequencies and different bias currents of the CCCCTAs. Monte Carlo analyses were also performed to examine the circuit's robustness against passive element tolerances. Additionally, the non-volatile behavior of the proposed memtranstor was confirmed through simulation results. For hardware validation, a bench prototype built using commercial off-the-shelf ICs reproduces the expected phi-q fingerprints, confirming its practicality. As an application, the emulator is embedded in a Chua oscillator, where simulations demonstrate rich nonlinear dynamics. To further verify the system's practical utility, a secure image encryption scheme is implemented, exhibiting high entropy and good statistical randomness properties. The combination of a resistorless design, dual current-domain control, experimental feasibility, and verified cryptographic applicability highlights the MT emulator as a compact building block for memory-augmented analog and chaos-based circuits.
Keywords: Memtranstor emulator; Memelements; Non-volatile behavior; Chaotic oscillator; Pinched hysteresis loop; Image encryption; MEMORY; VOLATILE; Computer Science; Engineering